The Influence of Competence, Compensation, and Leadership Style on the Performance of Village Officials in North Candi Laras District - Muhammad Fajeri; Misransyah Akos; Moh. Heru Budihantho; Nuril Mawaddah; Muhammad Jamili (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2026)
Village apparatus performance is a crucial factor in supporting the effectiveness of village governance and the quality of public services. However, several issues remain evident, including low attendance rates, delays in administrative reporting, and suboptimal public service performance among village officials in North Candi Laras District. This study aims to examine the effects of employee competence, compensation, and leadership style on village apparatus performance in North Candi Laras District, Tapin Regency. A quantitative approach with an explanatory research design was employed. The study involved 54 village apparatus members selected through a stratified random sampling technique. Data were collected using questionnaires and analyzed through multiple linear regression. The results reveal that employee competence, compensation, and leadership style each have a positive and significant effect on village apparatus performance. Simultaneously, these three variables also exert a significant influence on performance improvement. The findings indicate that enhancing employee competence, providing fair compensation, and implementing effective leadership practices are essential factors in improving village apparatus performance. This study contributes to the human resource management literature in the public sector, particularly in the context of village governance.